PENGARUH CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP PROFITABILITAS BANK YANG GO PUBLIC DI INDONESIA PERIODE 2009-2012 - Hamidah Hamidah; Erwinda Sari Purwati; Umi Mardiyati (Jurnal Riset Manajemen Sains Indonesia, 2013)
The Objective of this study were to examine the effects of corporate governance and leverage on profitability banking companies. The samples from this study is the banking company located in Indonesia are listed in Indonesia Stock Exchange (BEI) in the period 2009-2012. Corporate Governance mechanisms such as: board of directors, independent commissioners, institutional ownership and managerial ownership, and leverage on profitability (proxies by return on assets). These results indicate that the board of directors have negative and insignificant effect on return on assets. Independent commissioners have a positif and insignificant effect on return on assets. The proportion of institutional ownership, the proportion of managerial, and Leverage have negative and significant. The results show that corporate governance and leverage have simultaneously effect on return on assets of the banking company.